2017
DOI: 10.1002/srin.201700395
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Recrystallization and Flow Behavior in Low Carbon Nb–Ti Microalloyed Steel

Abstract: Single-pass hot compression tests are performed to study the hot deformation behavior of a low carbon microalloyed steel at temperatures in the range of 950-1050 C and strain rate from 0.01 to 0.5 s-1. Based on true stressstrain data, the effect of strain rate and temperature on the flow behavior of this steel is analyzed and peak stress is determined as well. The partial derivative of the strain hardening rate to stress is used to determine the critical stress. The value of activation energy and the ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…However, at the strain rate of 0.1, 1, and 10 s -1 , DRX behavior stayed incomplete and the unrecrystallization grains are illustrated in Figure 10 by the white arrows. It was for that higher strain rates, to some extent, brought less time for the movements of grain boundaries and dislocations, which restrained the growth of DRX nuclei [38,39]. Figure 11 illustrate the new recrystallized DRX grains and un-recrystallized grains, respectively.…”
Section: Microstructure Observationsmentioning
confidence: 99%
“…However, at the strain rate of 0.1, 1, and 10 s -1 , DRX behavior stayed incomplete and the unrecrystallization grains are illustrated in Figure 10 by the white arrows. It was for that higher strain rates, to some extent, brought less time for the movements of grain boundaries and dislocations, which restrained the growth of DRX nuclei [38,39]. Figure 11 illustrate the new recrystallized DRX grains and un-recrystallized grains, respectively.…”
Section: Microstructure Observationsmentioning
confidence: 99%
“…Unfortunately, the basic assumption that microstructure after deformation should be homogeneous and fully composed of equiaxed recrystallized grains regardless of recrystallization occurring or not inconsistent with the actual mixed microstructure consisting of both equiaxed recrystallized and elongated nonrecrystallized grains, [11][12][13][14] indicating that the austenite microstructural heterogeneity caused by partial recrystallization is not taken into consideration in the conventional methods. Furthermore, the macroscale microstructural states revealed in Sellars's work cannot provide a direct view of their evolutions due to lack of details; [15][16][17][18] therefore, other microscale microstructural features, such as the sizes and their distributions of both equiaxial and elongated grains, and the mixed fraction of microstructure must be employed to describe the microstructural state more precisely.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the effective content of Ti was reduced, and the precipitation strengthening of TiC was weakened. [5,6] To solve the adverse effects, Zr can be added to Ti-microalloyed steel to preferentially combine with O and S to form ZrO 2 and ZrS. [7,8] Previous studies have shown that the addition of Zr was able to prevent the growth of austenite grains at reheating temperatures.…”
Section: Introductionmentioning
confidence: 99%